2015
DOI: 10.1007/s11999-015-4250-9
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Magnitude and Long-term Economic Cost of Care of the British Military Afghanistan Amputee Cohort?

Abstract: BackgroundPersonal protection equipment, improved early medical care, and rapid extraction of the casualty have resulted in more injured service members who served in Afghanistan surviving after severe military trauma. Many of those who survive the initial trauma are faced with complex wounds such as multiple amputations. Although costs of care can be high, they have not been well quantified before. This is required to budget for the needs of the injured beyond their service in the armed forces.Question/purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 18 publications
0
50
0
Order By: Relevance
“…These interventions could have a great impact on resource utilization as patients managed following principles of DCR may require a longer intensive care unit and hospital stay and thus, higher medical resources and costs. As for complications, previous studies have investigated the impact of war on medical and economic resources [23][24][25] . For example, Edwards et al 24 , calculated the long-term cost of traumatic amputations of British personnel from Afghanistan and found that the total cost of 265 casualties that sustained a total of 416 amputations would be higher than USD 444 million over forty years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These interventions could have a great impact on resource utilization as patients managed following principles of DCR may require a longer intensive care unit and hospital stay and thus, higher medical resources and costs. As for complications, previous studies have investigated the impact of war on medical and economic resources [23][24][25] . For example, Edwards et al 24 , calculated the long-term cost of traumatic amputations of British personnel from Afghanistan and found that the total cost of 265 casualties that sustained a total of 416 amputations would be higher than USD 444 million over forty years.…”
Section: Discussionmentioning
confidence: 99%
“…As for complications, previous studies have investigated the impact of war on medical and economic resources [23][24][25] . For example, Edwards et al 24 , calculated the long-term cost of traumatic amputations of British personnel from Afghanistan and found that the total cost of 265 casualties that sustained a total of 416 amputations would be higher than USD 444 million over forty years. Masini et al 25 , showed that combat-related extremity injuries require the greatest utilization of resources for inpatient treatment, are responsible for a higher burden of disabled soldiers, and have the most significant projected disability benefit costs.…”
Section: Discussionmentioning
confidence: 99%
“…Edwards et al predicted the long-term (40 year) cost of trauma repair, rehabilitation, and lifelong prosthetic support of British soldiers wounded in Afghanistan to be approximately $444 million. 21 In the United States, the estimated average lifetime cost of treatment for unilateral lower LL is $342,716 and $1.4 million for Vietnam and OIF/OEF veterans, respectively.22 However, such estimates are likely conservative, not fully accounting for costs associated with novel technology/repairs or, perhaps exponentially more economically burdensome over the longer term, for the wide range of healthcare costs associated with the treatment of secondary health conditions. The ability to evaluate, predict, and ultimately treat these resultant health conditions would not only help reduce these costs but also, and most importantly, preserve and/or improve function and QoL for those with LL and LS.…”
mentioning
confidence: 99%
“…Of this total, an individual will spend $181,500 on prosthetics at approximately $10,232 per unit [13]. These costs are also corroborated in several unrelated studies on civilian and veteran lower limb amputation costs [5,19]. Similar estimates for upper limb amputations are not readily available in the literature.…”
Section: Introductionmentioning
confidence: 68%